Team Games Tournament (TGT) Model with Kelmat Media on Ratio Material for Grade VII in Mathematical Problem Solving - Shilvia Maslukhah; Choirudin Choirudin; Eka Fitria Ningsih; M. Saidun Anwar; Wawan Wawan; Agus Setiawan (Assyfa Journal of Islamic Studies, 2025)
Mathematics requires a strong conceptual understanding, especially in ratios, which often challenge seventh-grade students. This study examines the impact of the Team Games Tournament (TGT) learning model combined with KELMAT (Marble Mathematics) media on students' problem-solving skills. A quantitative approach with a pre-experimental design is employed. This study involves all seventh-grade students at SMP Ma'arif 1 Metro in the even semester of the 2024/2025 academic year. The sample is selected using cluster random sampling to ensure accurate representation. Research instruments include a problem-solving ability test and a student activity observation sheet. Data was collected through student activity observations and concept understanding tests. The analysis results indicate that H0 is rejected and H1 is accepted, as sig = 0.000 < α = 0.05. This indicates that the TGT model with KELMAT media significantly improves seventh-grade students' understanding of ratio concepts at SMP Ma'arif 1 Metro.